Effect of Dietary Proline on the Growth Performance, Collagen Deposition, and Texture Quality of Sea Cucumbers’ Body Wall (Apostichopus japonicus) - Rujian Xu; Zitong Wang; Haijing Liu; Ruixue Li; Xianyu Wang; Hongbing Yang; Jun Ding; Yaqing Chang; Rantao Zuo (Fishes, 2025)
Sea cucumber (Apostichopus japonicus) is an important economically cultured species in the northern coastal regions of China. Its body wall is rich in collagen, which directly determines product quality and market value. However, with the expansion of aquaculture scale, issues such as insufficient collagen deposition have led to inconsistent quality among cultured individuals. Therefore, there is an urgent need to improve growth performance and body wall quality through nutritional regulation. As functional nutrients, amino acids play key roles in collagen synthesis, yet relevant research on A. japonicus remains limited. This study was conducted to investigate the effects of dietary proline on the growth performance, body wall collagen deposition and organoleptic quality of sea cucumber (initial body weight: 30.20 ± 2.02 g). Three kinds of feed with equal levels of nitrogen and other lipids, and supplemented with different concentrations of proline (0%, 1.5%, 3%) in the basal diet, were named P0, P1.5, and P3, and the experiment was conducted for 60 days. The results showed that supplementation with 3% proline significantly increased final body weight and weight gain rate (p